Griscelli syndrome type 2: a novel mutation in gene with different clinical features in 2 siblings: a diagnostic conundrum - Kirtisudha Mishra; Shilpy Singla; Suvasini Sharma; Renu Saxena; Vineeta Vijay Batra (Korean Pediatric Society, 2014)
Griscelli syndrome type 2 (GS2) is a rare autosomal recessive disease caused by mutations in the RAB27A gene. It is characterized by cutaneous hypopigmentation, immunodeficiency, and hemophagocytic lymphohistiocytosis. We describe 2 brothers who had GS2 with clinically diverse manifestations. The elder brother presented with a purely neurological picture, whereas the younger one presented with fever, pancytopenia, hepatosplenomegaly, and erythema nodosum. Considering that cutaneous hypopigmentation was a common feature between the brothers, genetic analysis for Griscelli syndrome was performed. As the elder sibling had died, mutation analysis was only performed on the younger sibling, which revealed a novel homozygous mutation in the RAB27A gene on chromosome 15 showing a single-base substitution (c.136T>A p.F46I). Both parents were heterozygous for the same mutation. This confirmed the diagnosis of GS2 in the accelerated phase in both siblings. The atypical features of GS2 in these cases are a novel mutation, isolated neurological involvement in one sibling, association with erythema nodosum, and 2 distinct clinical presentations in siblings with the same genetic mutation.